Impedance mapping with high-density microelectrode array chips reveals dynamic heterogeneity of in vitro epithelial barriers - Alessandra Venz; Bastien Duckert; Liesbet Lagae; Saeedeh Ebrahimi Takalloo; Dries Braeken (Scientific Reports)
Abstract Epithelial tissues in vitro undergo dynamic changes while differentiating heterogeneously on the culture substrate. This gives rise to diverse cellular arrangements which are undistinguished by conventional analysis approaches, such as transepithelial electrical resistance measurement or permeability assays. In this context, solid substrate-based systems with integrated electrodes and electrochemical impedance monitoring capability can address the limited spatiotemporal resolution of traditional porous membrane-based methods. This label-free technique facilitates local, continuous, long-term analysis of tissue barrier properties for organ-on-chip applications. Increasing spatial resolution requires small electrodes arranged in a dense array, known as high-density microelectrode arrays (HD-MEAs). Integrated with Complementary Metal Oxide Semiconductor (CMOS) technology for multiplexing and rapid impedance measurements, HD-MEAs can enable high spatiotemporal resolution assessments of epithelial tissues. Here, we used 16,384 CMOS-integrated HD-MEA chip with subcellular-sized electrodes (8 μm diameter, 15 μm pitch, patterned in 16 clusters each consisting of 1024 electrodes in a 32 × 32 matrix) and impedance sensing capability to monitor dynamic evolution of Caco-2 cells, such as their proliferation, barrier formation, and 3D structure development on the chip. Changes in impedance at the selected frequency of 1 kHz (|Z| 1kHz ) enabled monitoring and analyzing the life cycle of Caco-2 cells grown on the HD-MEA chips (up to + 453% change after 7 days in culture). The |Z| 1kHz maps of proliferating Caco-2 cells and the differentiating epithelial tissue developing 3D domes aligned with the corresponding optical images at cellular resolution, which demonstrates the capability of the chip in tracking the dynamic heterogeneity of Caco-2 tissues in a label free and real-time fashion. Importantly, |Z| 1kHz maps acquired during chemically induced barrier disruption showed electrodes covered with 3D cell domes experienced a stronger decrease in impedance than those covered with adherent cells (-41% ± sd 10% against -16% ± sd 10%, respectively). This method could thus, in principle, enable detection of tissue barrier disrupting and modifying agents with higher specificity. Epithelial barrier function assays benefit from using HD-MEA impedance sensors due to their increased informativity and resolution, which will be of great value in future organ-on-chip platforms.